El Impacto de la crisis financiera global sobre las microfinanzas en el Perú - Nunura Chully, Juan Bautista (2015)
The objective of this research is to analyze the performance of microfinance institutions-IMF Peruvian in the run time and during the 2008- 2009 global financial crisis, and identify the determinants of lending rates of MFIs. The central hypothesis is that the performance of microfinance institutions is associated with economic conditions in the country and the international capital market. The other hypothesis is that the difference in rates between MFI lending interest is primarily associated administrative costs paid, the scale of loans, labor productivity, self-financing and credit experience. For what is first performed a descriptive analysis of MFI performance during the period 1994-2014 and then an explanatory analysis based on a multiple regression with panel data, whose source of information was published by the Superintendency of Banking and lnsurance. The regression results were as expected, that is, the performance of MFIs is associated with the cycle of the aggregate economy and also to fluctuations in the capital market of the United States and to a lesser extent market distortions capital emerging economies. The lending rate of MFIs would be determined mainly by the unit administrative costs, labor productivity, the credit history and risk of default in repayment of loans.